LAWANG FENOMENA INTERKULTURAL PADA PROSES KRATIF PENCIPTAAN KARYA MUSIK BARU - Gunawan, Arisko; Ismunandar, Ismunandar; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe creation of this work aims to allow individuals or groups of different cultures and comprehensionto open minds for a renewal for groups or individuals who will develop their knowledge, especially in the creative process of creating musical works.Lawang is a music program that includes extra musical objects that are realized into a work of musical composition. In the context of the musical aspect of this work is more dominated by occidental instrumentation (European-American) which is integrated into local cultural understanding in concept, technique, and philosophy. Lawang's works will be presented to the mixed musical ensembles. The steps used in the creation of this work include: preparation, incubation, illumination and verification with transferen and syncretic approaches. The Lawang music composition is a response to the intercultural phenomena which has the effects to the process of evolution of music science, especially, the creation of the music composition in Pontianak. The intercultural phenomena is the perspective that has been adopting as the framework of thinking in the creation of music which includes several characteristics such as open mindset and response to the coming and the development of the new knowledges which then realized. Keywords: Intercultural, Pontianak, Music Composition